基于集对理论的砂轮主轴转动系统故障树分析 - 刘英; 陈志恒; 陈宇 (Jixie chuandong)
On the basis of fault tree analysis of grinding wheel spindle rotation system,the set pair analysis theory considering the uncertain work state of random,mediation and unknown etc is injected,then the set pair-fault tree model combination of these two sets is established.Set of logic gates algorithm in model is deduced and the basic analysis process of the mode is given.The probability interval of grinding wheel spindle rotation system failure could be obtained through using connection number in token of the event status in the model.The results show that this method is more comprehensive,objective,and a good theoretical basis to reliability analysis of the grinding wheel spindle rotation system is provided.